Automatic Detection of Potholes and Speed Breakers - S, Monica; Nayak, Priyanka Govind; J, Pruthvi; K, Soumya; N, Venkatesh S (Perspectives in Communication, Embedded-systems and Signal-processing - PiCES, 2018)
One of the major problems in developing countries is maintenance of roads. Well maintained roads contribute a major portion to the country’s economy. Identification of pavement distress such as potholes and humps not only helps drivers to avoid accidents or vehicle damages but also helps authorities to maintain roads. The proposed system that have been developed and proposed a cost effective solution to identify potholes and humps on roads and provide timely alerts to drivers to avoid accidents or vehicle damages.IR sensor is used to detect the obstacles and hence avoid the accidents. Ultrasonic sensors are used to identify potholes and humps and also to measure their depth and height respectively. The system captures the geographical location coordinates of potholes and humps using GPS receiver. The sensed-data includes pothole depth, height of hump and geographical location. This serves as a valuable source of information to the Government authorities and to vehicle drivers. An android application is used to alert drivers so that precautionary measures can be taken to evade accidents. Alerts are given in the from a flash message with a audio beep.